2020
DOI: 10.1186/s12874-020-00998-w
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy cognitive mapping and soft models of indigenous knowledge on maternal health in Guerrero, Mexico

Abstract: Background: Effective health care requires services that are responsive to local needs and contexts. Achieving this in indigenous settings implies communication between traditional and conventional medicine perspectives. Adequate interaction is especially relevant for maternal health because cultural practices have a notable role during pregnancy, childbirth and the postpartum period. Our work with indigenous communities in the Mexican state of Guerrero used fuzzy cognitive mapping to identify actionable facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…Participants described culturally coherent responses to these risks including rituals, medicinal plants, massages, midwives counselling of husbands and other care practices connected with their culture. 56 …”
Section: Codesign Evaluate and Discuss: The Four-municipality Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants described culturally coherent responses to these risks including rituals, medicinal plants, massages, midwives counselling of husbands and other care practices connected with their culture. 56 …”
Section: Codesign Evaluate and Discuss: The Four-municipality Trialmentioning
confidence: 99%
“…Participants described culturally coherent responses to these risks including rituals, medicinal plants, massages, midwives counselling of husbands and other care practices connected with their culture. 56 The final statistical analysis of the randomised controlled trial, to be reported in a separate publication, will incorporate traditional midwifery knowledge as described in the fuzzy cognitive maps as prior knowledge in the statistical models, in an extension of Bayesian procedures. 57 This allows a space for Indigenous voices even in the very technical matter of effect estimation and significance testing.…”
Section: Codesign Evaluate and Discuss: The Four-municipality Trialmentioning
confidence: 99%
“…A study in the south of Guerrero included 29 Indigenous traditional midwives from the Me'phaa (Tlapaneco) and Nancue ñomndaa (Amuzgo) groups. 36 These women and two men had de facto recognition as midwives in their communities, based on their decades of service and traditional knowledge. Most used only Indigenous languages and the mapping session relied on trained intercultural brokers for translation.…”
Section: Resultsmentioning
confidence: 99%
“…The contextualisation of available evidence combined three sources of information—traditional midwives, 36 intercultural researchers working on perinatal care 33 and the available literature—to identify the influences on maternal health in Indigenous communities in southern Mexico. Traditional midwives contributed a cultural perspective grounded in Guerrero local conditions, and intercultural researchers shared their understanding of the issues, based on their years of bridging the relationships between Western institutions and Indigenous communities in their international work in America, Africa and Asia.…”
Section: Methodsmentioning
confidence: 99%
“… 57 Figure 1 illustrates a fuzzy cognitive map from traditional midwives in Guerrero state, describing their views about protective factors for maternal health. 58 …”
Section: Methodsmentioning
confidence: 99%